Genetic Structure of Endangered Species Anagallis foemina Mill. and Abundant Weed Anagalis arvensis L. Occurring in Segetal Habitats in South-Eastern Poland - Ewa Kwiecińska-Poppe; Sylwia Sowa; Joanna Lech; Małgorzata Haliniarz; Edyta Paczos-Grzęda (Agronomy)
In Poland, two species of the genus Anagallis can be found in segetal communities: scarlet pimpernel (Anagallis arvensis L.) and blue pimpernel (Anagallis foemina Mill.). A. arvensis usually has brick-red flowers and is a common weed in arable crops. Meanwhile, A. foemina, with blue flowers, is considered a species at risk of extinction in Poland. Flower colour is not a determinant of species affiliation, as there is a form of Anagallis arvensis f. azurea with blue flowers; thus, it is very difficult to specify the species identity of plants with blue flowers based on the negligible differences in morphology. Therefore, for the determination of species affiliation, the presence of two deletions within the intron of the chloroplastic gene trnL in A. arvensis and their absence in A. foemina were confirmed. The genetic similarity and population structure were established based on DNA polymorphism markers identified via the ISSR (inter simple sequence repeat) and SRAP (sequence-related amplified polymorphism) methods. UPGMA (unweighted pair group method with arithmetic mean) analyses revealed that red-flowered (A. arvensis) and blue-flowered (A. foemina) plants were grouped into two separate groups. Within the A. foemina group, two subgroups were distinguished: the first subgroup included genotypes from the Lublin Upland (LU) and Volhynian Polesie (VP), while the second subgroup consisted of genotypes from Western Volhynian Upland (VU). The within-group genetic diversity of A. arvensis was greater than the diversity within the A. foemina subpopulations. Principal coordinate analysis (PCoA) and STRUCTURE were also used to group samples according to species affiliation and collection site. The results obtained confirm that A. foemina populations in the study area are fragmented and isolated, which may lead to a decrease in their adaptability to environmental changes, reduced reproductive rates, and increased mortality.